Validity and Reliability of Adolescents Academic Inertia Scale - Özlem Tagay (International Journal of Psychology and Educational Studies, 2022)
The present study is about the development of Academic Inertia Scale for Adolescents (AADS) as well as analysis of its validity and reliability. The participants of the study were 410 students, 234 girls and 176 boys, enrolled at the 9th, 10th, 11th, and 12th grades in Anatolian high schools within the Meram district of Konya throughout the 2019-2020 academic year. A five-dimensional scale was obtained with a 46.96% variance explanatory power subsequent to the analyses of the factor structure,  explanatory and he confirmatory factor values sufficiently fitting to the model ((X2=516.28, sd=265, p=.000; RMSEA= 0,05, GFI=0,91, AGFI=0,89, CFI=, 0,94, NNFI=0,93, RMR= 0,09 ve SRMR= 0,05). In order to determine the internal consistency of the scale, Cronbach Alpha internal consistency coefficient was calculated as (.83), two half reliability as (.76) and test retest reliability as (.87) determining that the scale had sufficient reliability values .In line with the findings of the present study, further recommendations have been made  for researchers and practitioners.